BRAND EQUITY, FACE SAVING DAN SOCIAL INFLUENCE TERHADAP FASHION LUXURY CONSUMPTION PADA GENERASI MILLENNIAL - Nila Pusvikasari (E-Jurnal Manajemen Trisakti School of Management (TSM), 2021)
The objective of this study is to examine the effect of fashion luxury consumption such as brand equity ( there are brand loyalty, perceived quality, and brand knowledge), face saving and social influence. empirically, this study examines the effect of the dimension of brand equity on customers willingness to pay apremium price through an affective attitude, in addition to testing face saving and social influence on customer’s willingness to pay a premium price on the millennial generation in Jakarta, a total of 211 respondents in both online and offline surveys with Structurl Equation Modeling (SEM). This technique is used to test the causal relationship between contract in a structural model. The findings show that perceived quality and brand knowledge have an effect of affective attitude. Affective attitude, face saving, and social influence also have an effect of willingness to pay a premium price for luxury brands, while brand loyalty has no effect of affective attitude. Research limitations in this study are only tested on the luxury fashion industry and only tested for millennials generation. To research the effect of willingness to pay a premium price, further researcher should add other dimensions such as the brand association and to be carried out in all other luxury industries and all generations in Indonesia